TASAWWUF AHL AL-SUNNAH WA AL-JAMAAH - Muhammad Khairi Mahyuddin (IAI Al-Mawaddah Warrahmah Kolaka, 2019)
Tasawwuf is a knowledge that always misunderstood by society. There is a negative meaning and terminology regarding tasawwuf as a knoweledge that absorbed from other religion and deviant teaching. This writing is anrratif and discriptif elobaraltion deducted from Islamic literature. The finding of this writing faind out that tasawuf is s true knowledge based on Al-Qur’an and al Sunnah dan acceptable by scholars from Ahl al-sunnah wa al-Jama’ah